Smart blockchain : second international conference, SmartBlock 2019, Birmingham, UK, October 11-13, 2019, Proceedings /: second international conference, SmartBlock 2019, Birmingham, UK, October 11-13, 2019, Proceedings. (2019) - Unknown
No abstract available